1981
DOI: 10.1073/pnas.78.2.981
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of an herbicide receptor protein in chloroplast membranes

Abstract: ABSTRACT2-Azido-4 -ethylamino-6 -isopropylamino-s-triazine (azido-atrazine) inhibits photosynthetic electron transport at a site identical to that affected by atrazine (2-chloro4-ethylamino-6-isopropylamino-s-triazine). The latter is a well-characterized inhibitor of photosystem II reactions. Azido-atrazine was used as a photoaffinity label to identify the herbicide receptor protein; UV irradiation of chloroplast thylakoids in the presence of azido ['4C] Many commercial herbicides inhibit photosynthetic electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0
5

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(138 citation statements)
references
References 22 publications
(26 reference statements)
7
126
0
5
Order By: Relevance
“…The inhibitors ophenanthroline and terbutryn were found by X-ray studies to bind within Q~ site in R. viridis RC [5,6]. These structural studies confirmed and extended the previous proposals based (1) on photoaffinity labelling with azido-atrazine which binds to the L and D1 subunits [7,8] and (2) on the localization of almost all mutations conferring herbicide resistances which map to the part of genes coding for L and D1 residues located in the QB site [9 11]. …”
Section: Introductionsupporting
confidence: 84%
“…The inhibitors ophenanthroline and terbutryn were found by X-ray studies to bind within Q~ site in R. viridis RC [5,6]. These structural studies confirmed and extended the previous proposals based (1) on photoaffinity labelling with azido-atrazine which binds to the L and D1 subunits [7,8] and (2) on the localization of almost all mutations conferring herbicide resistances which map to the part of genes coding for L and D1 residues located in the QB site [9 11]. …”
Section: Introductionsupporting
confidence: 84%
“…The secondary structures of the L-and M-subunits have been confirmed by the elucidation of the crystal structure of the Rhodopseudomonas viridis reaction centre by Michel, Deisenhofer and colleagues [32,33]. Moreover, a close functional similarity between the bacterial and eukaryotic reaction centres has long been assumed, based on spectrophotometric analyses of the electron acceptor reactions (see [34]) and on their similar sensitivities to triazine herbicides [35,36].…”
Section: A Possible Functional and Structural Relationship Between Thmentioning
confidence: 95%
“…Embora ametrina, metribuzin, diuron e tebuthiuron tenham o mesmo mecanismo de ação, o sítio específico de ação desses herbicidas junto à quinona Qb é diferenciado (Christoffoleti et al, 2001). Portanto, essa pode ser a razão de ametrina e metribuzin com o mesmo mecanismo de ação (Pfister et al,1981;Oettmeier et al, 1984) Existem pelo menos quatro mecanismos gerais que podem explicar a resistência e/ou tolerância de plantas daninhas a herbicidas e influenciar o modo de ação desses compostos: baixa concentração do herbicida no local de ação; menor absorção e/ou translocação do herbicida; maior metabolização e/ou detoxificação do herbicida a substâncias menos tóxi-cas (De Prado et al, 1990;Sherman et al, 1996); e perda de afinidade do herbicida pelo sítio de ação específico (Sherman et al, 1996). Nesse sentido, Dias et al (2003) desenvolveram trabalho sobre tolerância de espécies de capim-colchão aos herbicidas aplicados na cultura da cana-de-açúcar, avaliando aspectos de eficácia de herbicidas e estudo dos mecanismos de tolerância.…”
Section: Implicações Sobre O Manejounclassified